(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2016)
This study aims at finding out to what extent DASH method improves students’ reading comprehension and how good the students’ improvement regarding their reading comprehension after taught through DASH method. This study was conducted at SMAN 1 Tanete Rilau, Barru Regency. The study used pre-experimental design involving only one class to observe, out of two hundred-eighty population of eleventh-grade students of IPA-II classes at SMAN-1 Tanete Rilau in academic year 2014/2015. The technique sampling was cluster random sampling. The instruments of collecting data used in this study were multiple choice and essay which were used to measure the students’ comprehension in reading. Based on the data collected from the students showed that the post-test value is higher than pre-test table, so the null hypothesis is rejected. It means there is an influence of “DASH” (Duplicated Answer Sheets) method on student reading ability. So the students have responsibility and feel enjoy the learning process. It means that can “DASH” (Duplicated Answer Sheets) method be used as one of the alternatives to teach reading. Further study is suggested to conduct the investigation of other teaching method or strategy that can be applied by the teacher to encourage their student in reading comprehension. Keywords: DASH Method, Reading Comprehension